ATM Transaction Security System Using Biometric Palm Print Recognition and Transaction Confirmation System (International Journal of Engineering and Computer Science, 2014)
Biometrics-based authentication offers several advantages over other authentication methods, there has been a significant surge in the use of biometrics for user authentication in recent years. In this project the existing security of the ATM (Automated Teller Machine) system has been improved by integrating the palm print of the user into the bank’s database as to further authenticate it. This was achieved by modeling and building an ATM simulator that will mimic a typical ATM system. The end result is an enhanced biometric authenticated ATM system that ensures greater security and increased customer’s confidence in the banking sector